2003
DOI: 10.1038/sj.ejhg.5200950
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XI sequence variations in nonsyndromic cleft palate, Robin sequence and micrognathia

Abstract: Cleft palate is a common birth defect, but its etiopathogenesis is mostly unknown. Several studies have shown that cleft palate has a strong genetic component. Robin sequence consists of three of the following four findings: micrognathia, glossoptosis, obstructive apnea, and cleft palate. While cleft palate is mainly nonsyndromic, about 80 percent of Robin sequence cases are associated with syndromes. Mutations in genes coding for cartilage collagens II and XI, COL2A1, COL11A1 and COL11A2, have been shown to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…Further evidence for this conclusion is apparent in the Cho mice, which exhibit excess mineralization in the long bones (Seegmiller et al, 1971;Li et al, 1995). Sequence variations in the Col11a1 gene are also associated with osteoarthritis, early-onset osteoarthritis, degenerative lumbar spinal stenosis and cleft palate (Melkoniemi et al, 2003;Noponen-Hietala et al, 2003;Rodriguez et al, 2004;Jakkula et al, 2005). Its association with a variety of common diseases makes Col11a1 an important target for musculoskeletal disease research.…”
Section: Discussionmentioning
confidence: 98%
“…Further evidence for this conclusion is apparent in the Cho mice, which exhibit excess mineralization in the long bones (Seegmiller et al, 1971;Li et al, 1995). Sequence variations in the Col11a1 gene are also associated with osteoarthritis, early-onset osteoarthritis, degenerative lumbar spinal stenosis and cleft palate (Melkoniemi et al, 2003;Noponen-Hietala et al, 2003;Rodriguez et al, 2004;Jakkula et al, 2005). Its association with a variety of common diseases makes Col11a1 an important target for musculoskeletal disease research.…”
Section: Discussionmentioning
confidence: 98%
“…Most newborns with Pierre Robin Sequence also exhibit respiratory and feeding difficulties. Cases of Pierre Robin Sequence are both phenotypically and genetically heterogeneous (Cohen, 1999;Houdayer et al, 2001;Jakobsen et al, 2006;Jamshidi et al, 2004;Melkoniemi et al, 2003;Ounap et al, 2005;Ricks et al, 2002). Pierre Robin Sequence can occur as an isolated nonsyndromic form, or can occur in combination with other syndromes.…”
Section: Snai1/2-dko Embryos As a Model For Pierre Robin Sequencementioning
confidence: 99%
“…Pierre Robin Sequence can occur as an isolated nonsyndromic form, or can occur in combination with other syndromes. Mutations in several collagen genes, including COL2A1, COL11A1 and COL11A2, have been found in subjects with nonsyndromic Pierre Robin Sequence (Melkoniemi et al, 2003), although it has not been established definitively that these mutations are causal for the observed malformations. In addition, chromosomal translocations (Jamshidi et al, 2004), duplications (Ounap et al, 2005) and deletions (Houdayer et al, 2001) have been described that are associated with nonsyndromic Pierre Robin Sequence.…”
Section: Snai1/2-dko Embryos As a Model For Pierre Robin Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…In humans, cleft palate due to mechanical interference with palatal shelf elevation by a malpositioned tongue and small jaw is clinically classified as Pierre Robin sequence or syndrome (PRS) (Rangeeth et al, 2011). Studies of human patients have shown that mutations in SATB2, SOX9, BMP2 and the collagens lead to PRS-like clefting (Melkoniemi et al, 2003;Tan et al, 2013). The etiology of PRS has also been associated with a range of syndromes and chromosomal anomalies plus extrinsic fetal deformational forces, but the developmental mechanisms causing this condition are unclear, in part because of the lack of an animal model (Tan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%